Record of Stephanitis takeyai Drake & Maa (Heteroptera Tingidae) on Pieris japonica (Thunb.) D. Don introduced in ltaly (Bollettino di zoologia agraria e bachicoltura, 2024)
Stephanitis takeyai Drake & Maa is reported on bonsai of Pieris japonica (Thunb.) D. Don from Japan. The adults were collected in October 2000.
Keywords: Stephanitis takeyai; Tingidae; Pieris japonica